Effect of thermal annealing on the interface quality of Ge/Si heterostructures. (September 2019) - Arroyo, Rojas Dasilva; Isa, Fabio; Isella, Giovanni; Erni, Rolf; von Känel, Hans; Gröning, Pierangelo; Rossell, Marta D.
Abstract: The performance of X-ray imaging detectors based on epitaxial Ge-crystal arrays grown on patterned Si substrates is severely limited by the presence of misfit and threading dislocations. Here, we study the effect of cyclic thermal annealing on misfit dislocations at the Ge/Si interface. By scanning transmission electron microscopy and energy dispersive X-ray spectroscopy, it is shown that the annealing process promotes the diffusion of Si into the Ge crystal resulting in a corrugated interface and slightly reduces the dislocation density. Finally, our results demonstrate that the thermal process is very effective at eliminating twin boundaries. Graphical abstract: Unlabelled Image